2007
DOI: 10.1007/s00253-007-1083-9
|View full text |Cite
|
Sign up to set email alerts
|

pH shock induces overexpression of regulatory and biosynthetic genes for actinorhodin productionin Streptomyces coelicolor A3(2)

Abstract: Actinorhodin production is markedly enhanced when an acidic pH shock is applied to a surface-grown culture of Streptomyces coelicolor A3(2). For an in-depth study of this phenomenon, transcriptional analyses using DNA microarrays and reverse transcription polymerase chain reaction and proteomic analysis were performed. Investigated were expression levels of the regulators and enzymes responsible for signal transduction and actinorhodin biosynthesis and enzymes involved in some major metabolic pathways. Regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…It is well known that environmental signals, including pH shock, can stimulate and promote the biosynthesis of secondary metabolites. Kim et al (2007) reported that when the pH was maintained at 5, production of geldanamycin was increased from 414 to 768 mg/L. Nadia et al (2004) studied the effects of temperature, pH, incubation period, some media and different nitrogen and carbon sources for the production of antimicrobial metabolite production.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that environmental signals, including pH shock, can stimulate and promote the biosynthesis of secondary metabolites. Kim et al (2007) reported that when the pH was maintained at 5, production of geldanamycin was increased from 414 to 768 mg/L. Nadia et al (2004) studied the effects of temperature, pH, incubation period, some media and different nitrogen and carbon sources for the production of antimicrobial metabolite production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, so-called "-omics-guided reverse engineering" approaches, including comparative transcriptomics and proteomics, were successfully used to identify alterations in gene expression associated with the overproduction of secondary metabolites in industrial streptomyces strains (9,10,11,12,13). Especially, interspecies genome-wide screening using S. coelicolor cDNA microarrays together with antibiotic-overproducing industrial strains of related streptomycetes led to the discovery of putative global downregulator genes affected by unidentified mutations in the industrial strains (9,14).…”
mentioning
confidence: 99%
“…It has been reported that production of the antibiotic actinorhodin was signiWcantly enhanced when an acidic pH shock was applied to surface cultures of S. coelicolor [20,21]. Among many over-expressed genes identiWed from S. coelicolor DNA microarrays [19,20], several Na + /H + antiporter genes including SCO7832 were also identiWed as pH-shock-induced potential target genes.…”
Section: Introductionmentioning
confidence: 99%
“…The well-characterized pathway-speciWc regulatory proteins including ActII-ORF4 for actinorhodin biosynthesis from S. coelicolor belong to the so-called Streptomyces Antibiotic Regulatory Proteins (SARPs) family [16]. Another important transcriptional family of regulators that belong to the so-called LAL (Large ATPbinding regulators of the LuxR) family have also been identiWed and characterized in several macrolide antibiotic pathways including TmcN for tautomycetin [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation